Moral religion: the later Ricoeur's hermeneutics of ethical life - Carter, J; James C. Carter (2011)
This thesis engages with the later writings of Paul Ricoeur in order to understand his philosophy as a whole. A reconstruction of Ricoeur’s hermeneutics of ethical life presents his significant contribution to contemporary philosophy of religion. This hermeneutics aims to elucidate a moral religion that binds humans together universally on the basis of the life they share as capable beings. To facilitate this hermeneutics, I will demonstrate that a selective reading of Ricoeur’s philosophy brings to light the pivotal role of his ‘little ethics’ in bridging his later and earlier works. The capable human (l’homme capable) in the later Ricoeur must be understood in relation to both the ‘little ethics’ and an architectonic of moral religion. Elucidating the aim (telos) of ethical life and the norm (‘moral law’) of moral religion from the ‘little ethics’ points to the significant roles of Aristotle and Kant in Ricoeur’s architectonic. Ricoeur himself defines ‘architectonic’ in Kantian terms as a critical framework, while appropriating Spinoza’s metaphysical conception of a rational striving ( conatus) for life in its fullness. Core concepts taken from Spinoza, Aristotle and Kant are implicit in the present reconstruction of Ricoeur’s hermeneutics. Three dimensions of ethical life emerge in Spinoza’s metaphysics, Aristotle’s anthropology, and Kant’s moral philosophy, giving us Ricoeur’s architectonic. For Ricoeur, the ethical aim is grounded on a metaphysics of human capability, and the demanding nature of ‘the law’ renders religion moral. This religion assumes that the good life is the goal of human striving. But crucially, the thesis will uncover ‘the arrow of the religious’ (la flèche du religieux) as it motivates the capable subject to embrace life with and for others in just institutions. In conclusion, life is revealed as the heart of Ricoeur’s moral religion.